2019
DOI: 10.1158/1535-7163.mct-18-0791
|View full text |Cite
|
Sign up to set email alerts
|

Altered Steroid Milieu in AI-Resistant Breast Cancer Facilitates AR Mediated Gene-Expression Associated with Poor Response to Therapy

Abstract: Divergent roles for androgen receptor (AR) in breast cancer have been reported. Following aromatase inhibitor (AI) treatment, the conversion of circulating androgens into estrogens can be diminished by >99%. We wished to establish whether the steroid environment can dictate the role of AR and the implications of this for subsequent therapy. This study utilizes models of AI resistance to explore responsiveness to PI3K/ mTOR and anti-AR therapy when cells are exposed to unconverted weak androgens. Transcriptomic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…Previous studies in postmenopausal breast cancer women have shown significantly high levels of circulating testosterone than the normal controls (37) and further showed the association of high testosterone levels with worse prognosis in ER positive post-menopausal women (38). Regulation of AR depends on the hormonal milieu, and it is hypothesized that the discordance between AR and ER based signaling may be regulated by relative availability of each receptor (39). Testosterone is a precursor for estrogens and is converted by aromatase to either estradiol or 5adihydrotestosterone (DHT) by the enzyme 5a reductase in the tumor microenvironment (40).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in postmenopausal breast cancer women have shown significantly high levels of circulating testosterone than the normal controls (37) and further showed the association of high testosterone levels with worse prognosis in ER positive post-menopausal women (38). Regulation of AR depends on the hormonal milieu, and it is hypothesized that the discordance between AR and ER based signaling may be regulated by relative availability of each receptor (39). Testosterone is a precursor for estrogens and is converted by aromatase to either estradiol or 5adihydrotestosterone (DHT) by the enzyme 5a reductase in the tumor microenvironment (40).…”
Section: Discussionmentioning
confidence: 99%
“…Recent preclinical and clinical studies indicate that AR could be a growth promoter in tamoxifen-resistant breast cancer, but a growth inhibitor in tamoxifen-sensitive breast cancer. Although AR antagonist enzalutamide increased proliferation of parental breast cancer cell line MCF-7, it inhibited proliferation of tamoxifen-resistant MCF-7 cells (Creevey et al., 2019). Similarly, tamoxifen-resistant clinical specimens that had higher AR:ER ratio had aggressive disease and poor prognosis (Cao et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…All ER signaling markers were significantly decreased from baseline to 4þmonths AI therapy (ESR1 P < 0.0001, FOXA1 P < 0.0001, GATA3 P < 0.001, IL6ST P < 0.001), whereas the breast cancer-specific AR signaling markers were increased or unchanged (GHR P < 0.01, PTGER3 P < 0.01, ADRA2A n.s, AR n.s). Using our previously published 4AD-regulated gene set (7), we further found that PKIB (P < 0.01) and SYTL4 (P < 0.01) were elevated in patients whose tumors developed acquired resistance compared with dormant tumors (Fig. 4C).…”
Section: Clin Cancer Res; 2021 Clinical Cancer Research Of6mentioning
confidence: 65%
“…5). In light of this, there is now renewed focus on alternate steroid facilitators of breast cancer progression (6,7), nongenomic steroid action (8) and also members of the nuclear receptor subfamily 3C, which includes the androgen receptor (AR; refs. [9][10][11].…”
Section: Introductionmentioning
confidence: 99%